Endodontic-periodontal continuum of tooth: Systematic literature review - D. A. Ostanina; S. Sh. Alimukhamedova; A. V. Mitronin (Эндодонтия Today, 2024)
INTRODUCTION. The pathogenetic relationship between periodontal and pulp diseases was first described by Simring and Goldberg in 1964. Since then, the term “endodontic-periodontal” lesion (or “endo-perio”) has been used to describe lesions caused by inflammatory products found to varying degrees in both the periodontal and dental pulp tissues. The pulp and periodontium have embryonic, anatomical and functional relationships. The simultaneous presence of changes in pulp tissue and inflammatory periodontal diseases can complicate diagnosis and treatment planning. The etiology, pathogenesis and treatment methods of endodontic-periodontal lesions can vary from quite simple to relatively complex aspects. Knowledge of the basis of concomitant inflammatory processes in the pulp and periodontium is important for making the correct diagnosis.AIM. Carry out a systematic analysis of the literature and summarize the available data on etiopatogenetic relations, diagnostic features and clinical history of endodontic periodontal dental lesions. MATERIAL AND METHODS. A systematic literature analysis was carried out, as well as a manual search in the databases PubMed, Google Search, eLibrary, disserCat, Cyberleninka. Among national and foreign publications corresponding to the topic of this review, 28 publications were selected for systematic analysis, the results of literature review are presented in this article.CONCLUSION. This systematic review found that dental anatomy and the etiology of endodontic periodontal lesions are the basis for difficulties in the diagnosis and treatment of patients with endo-periodontal lesions. Determining the prevalence of infection and the individual characteristics of EPP pathogenesis in patients in this group remains a challenge. In the future, it is necessary to develop new methods of diagnosis, prophylaxis and complex treatment of combined periodontal tissue and tooth pulp, which will improve the prognosis of treatment of injured teeth in the long term.